The factors of work stress among employee in TM Training Centre, Kuala Lumpur / Emilia Natasha Johari and Nur Amirah Umar - Johari, Emilia Natasha; Umar, Nur Amirah (Faculty of Business and Management, 2013)
Work stress becomes a common problem faced by employees in many organizations regardless any industry that they involves today. In this study, the researchers choose to identify the factor that influence work stress that occur in TM Training Centre, Kuala Lumpur. Workload, role conflict and interpersonal relationship at work are the factors that the researchers emphasized in this study. The researchers need to find out what are the relationships these factors with work stress and which one of these factor that most significant to work stress among employees in TM Training Centre. Thus, this study has conducted in TM Training Centre on 80 of respondents to be our sample. The findings of this study indicates workload is the factor that most significant to work stress in the organization. This study is beneficial to the organizations especially they are increase stress in their work. It will help them more aware on the main factor of their work stress and in turn help them manage the condition from getting worse. Future study should focus on the similar study but different factors to any organization in any industry. By doing this, we can get a clearer picture on the work stress matter occurred in many organizations in era of globalization.